ВОЈСКА У СЛУЖБИ ГЛОБАЛНОГ МИРА И БЕЗБЕДНОСТИ: ИНТЕРЕСОВАЊЕ И МОТИВАЦИЈА ЗА МУЛТИНАЦИОНАЛНЕ ОПЕРАЦИЈЕ - Radojević, Slobodan (Srpska politička misao, 2025)
The paper shows how the Serbian Armed Forces, through their participation in multinational (peacekeeping) operations, contribute to the improvement and maintenance of global peace and security under the auspices of the United Nations and the European Union, as well as the motivation and interest in peacekeeping operations. Furthermore, the research conducted at the Military Academy seeks to find the motives of the participants in the operations, as well as the motives that direct future officers to participate in multinational operations. For the purposes of this paper, Battistelli’s paradigm of premodern, modern, and postmodern motivational factors for participation in peacekeeping operations was applied. The author’s starting assumption is that the motivational factors for the participation of our members are in the domain of premodern (traditional) and modern. The paper first analyzes past and current operations in which our Army has participated and is an active participant in order to present the way in which the Serbian Armed Forces act in the service of global peace and security, and its role in that field. In the first part, the paper presents the rich historical experience of our Army’s participation in multinational operations. Considering that multinational operations are an instrument for preventing and containing crisis hotspots in the world, as well as preventing armed conflicts, they also contribute to countries’ international reputation. Furthermore, the paper presents and explains the understanding of the importance of multinational operations in our Army, through the importance of the role of the Serbian Armed Forces in preserving global peace and security, as well as emphasizing the impact of transferring experiences and knowledge gained in multinational operations. The significance of the research is that the authors confirm that the motivational factors for participation in multinational operations are strengthening the foreign policy reputation and international relations of our country, the general development of our Army and gaining valuable experience, as well as the financial position of the participants, which represents traditional and modern motivational factors.